2016
DOI: 10.1002/uog.15953
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal progesterone decreases preterm birth ≤ 34 weeks of gestation in women with a singleton pregnancy and a short cervix: an updated meta‐analysis including data from the OPPTIMUM study

Abstract: ObjectiveTo evaluate the efficacy of vaginal progesterone administration for preventing preterm birth and perinatal morbidity and mortality in asymptomatic women with a singleton gestation and a mid‐trimester sonographic cervical length (CL) ≤ 25 mm.MethodsThis was an updated systematic review and meta‐analysis of randomized controlled trials comparing the use of vaginal progesterone to placebo/no treatment in women with a singleton gestation and a mid‐trimester sonographic CL ≤ 25 mm. Electronic databases, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
168
1
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(190 citation statements)
references
References 71 publications
10
168
1
11
Order By: Relevance
“…Contrastingly, the OPPTIMUM study (n = 1228) found that prophylactic progesterone was not associated with reduced risk of PTB (adjusted OR 0.86, 95% CI 0.61 -1.22), and that childhood outcomes were not significantly different (mean difference in cognitive scores at 2 years old -0.48, 95% CI -2.77 -1.81) (65). A subsequent meta-analysis (n = 974) of five trials including the OPPTIMUM study found that progesterone decreased the risk of PTB ≤ 34 weeks (RR 0.66, 95% CI 0.52 -0.83) and had no adverse effects on neurodevelopmental outcomes (20). However, the study only included women with a short cervix (only 251 out of 1228 OPPTIMUM patients were included), and there remains uncertainty as to which populations benefit from progesterone.…”
Section: Progesteronementioning
confidence: 97%
See 1 more Smart Citation
“…Contrastingly, the OPPTIMUM study (n = 1228) found that prophylactic progesterone was not associated with reduced risk of PTB (adjusted OR 0.86, 95% CI 0.61 -1.22), and that childhood outcomes were not significantly different (mean difference in cognitive scores at 2 years old -0.48, 95% CI -2.77 -1.81) (65). A subsequent meta-analysis (n = 974) of five trials including the OPPTIMUM study found that progesterone decreased the risk of PTB ≤ 34 weeks (RR 0.66, 95% CI 0.52 -0.83) and had no adverse effects on neurodevelopmental outcomes (20). However, the study only included women with a short cervix (only 251 out of 1228 OPPTIMUM patients were included), and there remains uncertainty as to which populations benefit from progesterone.…”
Section: Progesteronementioning
confidence: 97%
“…A previous PTB or late miscarriage is a widely recognized risk factor for PTB, which could be linked to many mechanisms (3). Systemic maternal infections, urinary tract or intra-uterine infections, bacterial vaginosis, and douching may all disrupt the maternal vaginal microbiome and are linked with the release of pro-inflammatory factors, which are linked to increased rates of sPTB (3,8,20,21). Uterine and cervical weakness impair their ability to support mechanical stresses induced by full-term pregnancy.…”
Section: Aetiology and Risk Factors For Ptbmentioning
confidence: 99%
“…Прогестерон по-зитивно впливає на процеси інвазії трофобласту шляхом стимуляції росту та ремоделювання спіральних артерій, а також посилення експресії VEGF, що покращує процеси ан-гіогенезу; забезпечує баланс ангіогенних факторів -VEGF та PEGF; збільшує синтез NO ендотеліальними клітинами, і як наслідок -сприяє оптимальному кровообігу в матці й адап-тації її ендотелію до оптимальної імплантації та розвитку ва-гітності [1,9].…”
Section: вплив прогестерону на інвазію трофобластуunclassified
“…У 2016 році в престижному міжнародному виданні Ultrasound Obstet Gynecology були опубліковані результа-ти оновленого мета-аналізу R. Romero та співавторів [9], доповнені індивідуальними даними пацієнток з короткою шийкою матки, які отримували Утрожестан в дозі 200 мг на добу з метою профілактики ПП. Було показано, що вагіналь-…”
Section: прогестерон для профілактики та лікування невиношування вагіunclassified
“…Интравагинальное введе-ние прогестерона также рассматривается как эффективный подход к снижению показателя преждевременных родов при длине шейки мат-ки ≤ 25 мм, установленной при ультразвуковом исследовании в средних сроках беременно-сти [9]. Необходимо отметить, однако, что на-личие признаков преждевременных родов при короткой шейке матки может являться показа-нием для терапии прогестероном, но не церви-кального серкляжа, для которого должен также присутствовать критерий невынашивания бе-ременности в анамнезе [5].…”
Section: до леченияunclassified